The Guardian of Constitution: A Comparative Perspective of Indonesia and Cambodia - Sampe, John; Ristawati, Rosa; Hakyou, Be (Faculty of Law, Hasanuddin University, 2023)
A democratic state may be indicated by the existence of a constitutional institution that has the competence to uphold constitutionalism and defend the constitution. As the guardian of the constitution, the Constitutional Council of the Kingdom of Cambodia (Constitutional Council) and the Constitutional Court of the Republic of Indonesia (Constitutional Court) have the same purpose, namely to uphold constitutionalism and protect the constitution. However, in terms of structure, procedures, and competencies, the Constitutional Council and the Constitutional Court have individual mechanisms. Institutionally, the two judicial bodies occupy different characteristics, but they share the common goal of safeguarding the constitution’s core values. This paper aims to analyze and scrutinize different features of the Constitutional Council and the Constitutional Court by showing the same purpose as the guardian of the constitution. Within this paper, the legal outcomes which is decisions are discussed, particularly the effect of the decisions. In addition, this paper looks into who can be the applicant or can file a complaint and clarifies the qualifications and resignations of judges. This paper concludes on whether the Constitutional Court and the Constitutional Council have different paths in upholding constitutionalism and protecting the constitution.